2008
DOI: 10.3748/wjg.14.795
|View full text |Cite
|
Sign up to set email alerts
|

Portalsystemic hemodynamic changes in chronic severe hepatitis B: An ultrasonographic study

Abstract: AIM:To evaluate portalsystemic hemodynamic changes in chronic severe hepatitis B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In one study, UVR incidence was found to be gradually increased from 0 to 22%, 56%, and 75% in patients with normal and chronic hepatitis patients to patients with compensatory cirrhosis, decompensation cirrhosis, and severe chronic liver disease, suggesting UVR had an impact on disease progress. [ 16 ] It was suggested that UVR directs blood entering the systemic circulation without liver detoxification, which may increase HE risks. [ 23 ] Based on the phenomenon that collateral circulation increases the incidence of HE, clogging of collateral vessel recanalization may be used to treat HE, and the ascites and esophageal varices do not significantly aggravate the HE incidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study, UVR incidence was found to be gradually increased from 0 to 22%, 56%, and 75% in patients with normal and chronic hepatitis patients to patients with compensatory cirrhosis, decompensation cirrhosis, and severe chronic liver disease, suggesting UVR had an impact on disease progress. [ 16 ] It was suggested that UVR directs blood entering the systemic circulation without liver detoxification, which may increase HE risks. [ 23 ] Based on the phenomenon that collateral circulation increases the incidence of HE, clogging of collateral vessel recanalization may be used to treat HE, and the ascites and esophageal varices do not significantly aggravate the HE incidence.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] The extrahepatic shunt is mainly related to extrahepatic portal angiogenesis, leading to the reopening of the traffic branch between the usually closed portal-vena cava system, and the collateral circulation being formed between the extracorporeal and the vena cava system. [15,16] One of the reopening channels is the umbilical vein. Finally, part of the portal vein blood flows into the vena cava and back into the heart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not uncommon to see compensatory reopening of the umbilical vein in the presence of cirrhotic portal hypertension 3, 4. Tumor thrombus formation into the portal and splenic veins is also very common in primary liver cancer,5–10 but there are few studies reporting tumor thrombus formation in the umbilical vein.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Tumor thrombus formation into the portal and splenic veins is also very common in primary liver cancer, [5][6][7][8][9][10] but there are few studies reporting tumor thrombus formation in the umbilical vein.…”
Section: Discussionmentioning
confidence: 99%